2016
DOI: 10.21276/sajb.2016.4.6.6
|View full text |Cite
|
Sign up to set email alerts
|

Animal Bite Cases in Western Rajasthan, India: A Retrospective Study 2009-2015

Abstract: Animal bites in humans are an important public health problem. Most of these bites are dog bites. Dog bites in humans are a complex problem embracing public health and animal welfare, both in developed and developing nations. In order to estimate the magnitude of the problem and to understand the epidemiological characteristics of dog bite victims registered in Anti Rabies Clinic of Dr. S.N. medical college, Jodhpur regarding their age, sex, number of registered dog bite victims per month and year along the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Dogs and cats caused most bites, accounting for 53.22 and 42.29% of reported bites respectively. Dogs were also the main cause in other countries; 65.9% in Tehran, Iran (Eslamifar et al, 2008) and 89.2% in Ilam Province, Iran (Eslamifar et al, 2008); 93.7% in Western Rajasthan, India (Singh et al, 2016); 85%-90% in the United States of America (Cook et al, 2020), 91.2% in Lebanon (Kassir et al, 2019) and 99.8% in Iraq (T, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Dogs and cats caused most bites, accounting for 53.22 and 42.29% of reported bites respectively. Dogs were also the main cause in other countries; 65.9% in Tehran, Iran (Eslamifar et al, 2008) and 89.2% in Ilam Province, Iran (Eslamifar et al, 2008); 93.7% in Western Rajasthan, India (Singh et al, 2016); 85%-90% in the United States of America (Cook et al, 2020), 91.2% in Lebanon (Kassir et al, 2019) and 99.8% in Iraq (T, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…8 The incidence of animal bites is 17.4 per 1000 population. A person is bitten every 2 seconds, and someone dies from rabies every 30 minutes.…”
Section: Introductionmentioning
confidence: 99%
“…10 Study conducted by Singh et al in Rajasthan found that dog bite contributed to (93.7%). 12 This indicates need of vaccinating the dogs.…”
mentioning
confidence: 99%